Model Pembinaan Moralitas Siswa melalui Kegiatan Ekstrakurikuler Keagamaan di Sekolah Berbasis Pesantren: Studi Kualitatif di Sekolah Menengah Pertama Birrul Walidain - Fauzan Fauzan; Hilmiati Hilmiati; M. Sobry Sutikno; Maimun Maimun (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Student moral development is a fundamental dimension of Islamic education, particularly in pesantren-integrated school environments. This study investigates the model of student moral cultivation through religious extracurricular activities at SMP Birrul Walidain, a pesantren-based school in Indonesia. Using a qualitative descriptive approach, data were gathered through in-depth interviews, participant observation, and document analysis involving the school principal, religious activity supervisors, Islamic scholars (ustaz/ustazah), and students. Findings reveal that moral cultivation is implemented through five structured religious activities: Al-Qur'an tahfiz (memorization), congregational prayer (shalat berjamaah), public speaking training (muhadharah), classical Islamic text study (kajian kitab), and Islamic social activities. These activities are underpinned by four methodological pillars: modeling (keteladanan), habituation (pembiasaan), moral guidance and motivation (nasihat), and disciplinary supervision (muraqabah). The pesantren environment significantly reinforces moral internalization. Key challenges include social media influence, diverse student backgrounds, and varying levels of religious motivation. The study concludes that integrated religious extracurricular programs within pesantren-based schools constitute an effective strategic framework for holistic moral character formation, with implications for Islamic educational policy and curriculum design in Indonesia.